2013
DOI: 10.1371/journal.pone.0063989
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Imaging of NADPH Oxidase Activity in Living Cells Using a Novel Fluorescent Protein Reporter

Abstract: Production of reactive oxygen species (ROS) has been implicated in the pathology of many conditions, including cardiovascular, inflammatory and degenerative diseases, aging, muscular dystrophy, and muscle fatigue. NADPH oxidases (Nox) have recently gained attention as an important source of ROS involved in redox signaling. However, our knowledge of the source of ROS has been limited by the relatively impoverished array of tools available to study them and the limitations of all imaging probes to provide meanin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(91 citation statements)
references
References 31 publications
6
84
0
1
Order By: Relevance
“…Genetic knock-out of p47 phox attenuates ROS generation in skeletal muscle 17 . Therefore, we hypothesized that genetic abrogation of p47 phox function in mdx mice would be beneficial against oxidative stress-induced damage.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic knock-out of p47 phox attenuates ROS generation in skeletal muscle 17 . Therefore, we hypothesized that genetic abrogation of p47 phox function in mdx mice would be beneficial against oxidative stress-induced damage.…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, cellular responses mediated by the Nox2 isoform of NADPH oxidase are absent in neutrophils, macrophages, and skeletal muscle of p47 phox(−/−) mice (Huang et al, 2000; Jackson et al, 1995; Pal et al, 2013). The lack of oxidative burst in neutrophils and macrophages renders p47 phox(−/−) mice immunocompromised and increases susceptibility to infection (Huang et al, 2000).…”
Section: Methodsmentioning
confidence: 99%
“…In coronary arteries, NADPH oxidase is responsible for impaired vasodilation caused by SMase. Diaphragm expresses the Nox2 isoform of NADPH oxidase (Javesghani et al, 2002) and recent studies have shown that the enzyme is important for oxidant production during muscle contraction and stretch (Michaelson et al, 2010; Pal et al, 2013; Sakellariou et al, 2013). Based on the emerging role of NADPH oxidase in modulating skeletal muscle function and our preliminary data, we conducted the current study to test the hypotheses that NADPH oxidase mediates the increase in oxidants and decrease in force of skeletal muscle exposed to SMase.…”
Section: Introductionmentioning
confidence: 99%
“…Mitochondria are traditionally considered to be the major site for O 2 †2 production in contracting skeletal muscle and this viewpoint is, for instance, supported by recent studies employing either mitochondrial-targeted O 2 †2 indicator or antioxidant Cheng et al 2015). On the other hand, other recent studies propose NADPH-oxidase 2 (NOX2) as the main ROS source in contracting skeletal muscles, because the contraction-mediated ROS increase was prevented by pharmacological inhibition or genetic knockdown of NOX2 (Michaelson et al 2010;Pal et al 2013;Sakellariou et al 2013). Thus, the relative importance of different sources of O 2 †2 in contracting muscle remains uncertain.…”
Section: The Primary Ros In Cells Are the Superoxide Anion (O 2 †2mentioning
confidence: 92%
“…Because of these problems, methods based on high-pressure liquid chromatography (HPLC) have been recommended (Kalyanaraman et al 2012), but such methods are impractical when following ROS/RNS over time, for example, during exercise and the subsequent recovery. Recently developed indicators based on genetically engineered fusion proteins may improve the situation, and a major attraction with these is that they can be targeted to specific organelles or proteins (Hanson et al 2004;Gutscher et al 2009;Meyer and Dick 2010;Pal et al 2013). …”
Section: Reactive Oxygen/nitrogen Speciesmentioning
confidence: 99%